2009
DOI: 10.1007/978-1-60761-350-3_14
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase 1 Interactions with HDL, Antioxidants and Macrophages Regulate Atherogenesis – A Protective Role for HDL Phospholipids

Abstract: Macrophage cholesterol accumulation and foam cell formation is the hallmark of early atherogenesis. In addition to macrophages, at least three more major players regulate atherosclerosis development; paraoxonase 1 (PON1), antioxidants, and HDL. PON1 is an HDL-associated lactonase which posses antioxidant and anti-atherogenic properties. PON1 protects against macrophage-mediated LDL oxidation, and increases HDL binding to macrophages which, in turn, stimulates HDL's ability to promote cholesterol efflux. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 66 publications
2
33
0
1
Order By: Relevance
“…Paraoxonase 1 (PON1) is an HDL-associated lactonase harboring anti-oxidant and anti-atherogenic properties ( 34 ). PON1 increases HDL binding to macrophages which, in turn, promotes HDLmediated cholesterol effl ux ( 34 ).…”
Section: Exposure To Ufps Reduced Hdl Anti-oxidant Capacity and Pon Amentioning
confidence: 99%
See 1 more Smart Citation
“…Paraoxonase 1 (PON1) is an HDL-associated lactonase harboring anti-oxidant and anti-atherogenic properties ( 34 ). PON1 increases HDL binding to macrophages which, in turn, promotes HDLmediated cholesterol effl ux ( 34 ).…”
Section: Exposure To Ufps Reduced Hdl Anti-oxidant Capacity and Pon Amentioning
confidence: 99%
“…Paraoxonase 1 (PON1) is an HDL-associated lactonase harboring anti-oxidant and anti-atherogenic properties ( 34 ). PON1 increases HDL binding to macrophages which, in turn, promotes HDLmediated cholesterol effl ux ( 34 ). The ability of HDL to inhibit LDL oxidation and lipid peroxidation is mediated, in part, through PON ( 35 ).…”
Section: Exposure To Ufps Reduced Hdl Anti-oxidant Capacity and Pon Amentioning
confidence: 99%
“…It has been shown that small HDL3 particles have higher PON1 antioxidant activity than large HDL2 particles 18) . This protective effect is mediated by HDL and its associated proteins as PON1 19) . However, it is also known that there is an inverse relationship between HDL-C and the risk of CAD development 20) .…”
Section: Subjectsmentioning
confidence: 99%
“…The scavenger receptor class B type 1 (SR-B1) represents an alternate pathway for HDL-mediated cholesterol efflux. While PON1 protects HDL and LDL particles against oxidation, it also enhances RCT by facilitating the binding of HDL particles to macrophages (2224). Incubation of J774A.1 macrophages with fluorescently labeled PON1 shows that PON1 binds to low-affinity sites and is internalized (25).…”
Section: Hdl Pon1 and Reverse Cholesterol Transportmentioning
confidence: 99%